Investigation on microstructure, mechanical and durability characteristics of recycled aggregate concrete with non-traditional supplementary cementitious materials / Mohammed F. E. Alnahhal - Mohammed F. E. , Alnahhal (2017)
The use of supplementary cementitious materials (SCMs) from industrial and agricultural by-products as a partial replacement for conventional cement and recycled materials by concrete industry is viable alternative to sustainable development. The utilization of SCMs has become more intense in the concrete industry due to their better long-term properties. Thus, the increasing awareness and usage of traditional SCMs, such as fly ash, silica fume and ground granulated blast-furnace slag in concrete have pressured the construction industry to look for alternatives to overcome the concerns over their availability in the future. This research evaluates the performance of concrete that was developed using a high amount of recycled aggregate (RA) incorporated with non-traditional SCMs from agricultural wastes, namely rice husk ash (RHA), palm oil fuel ash (POFA) and palm oil clinker powder (POCP) as alternative sources of SCMs. Unlike previous investigations, that only concentrated on the effect of RA on performance of the concrete, this research presents the mechanical and durability properties of the RHA, POFA and POCP in RA-based concrete as well as their physical and chemical characteristics to draw meaningful relationships between SCMs properties and performance of RA-based concrete. The physical and chemical characteristics of these non-traditional SCMs were measured using techniques such as particle size analysis, scanning electron microscopy (SEM) imaging and x-ray fluorescence (XRF). In addition, SEM imaging and X-ray diffraction (XRD) analysis were used to characterize the microstructure of RA-based concrete containing SCMs. The variables investigated include different percentages of RHA, POFA and POCP at 10%, 20% and 30% cement replacement levels to investigate their effect on fresh and hardened concrete properties, as well as their ability to mitigate degradation resulting from different aggressive media like water absorption, acid attack, sulfate attack, penetration of chloride ions and elevated temperatures. In terms of fresh and hardened properties, the results showed that the 10% replacement level of cement by RHA produced the highest strength at all ages tested. Although POFA and POCP were found to negatively affect the strengths at an early age, the hardened properties showed improvement after a relatively long curing period of 90 days. However, the 90-day compressive strength of 30 MPa was achieved by using SCMs at levels up to 30%. In terms of durability properties, the results showed that the incorporation of RHA, POFA and POCP up to 30% minimizes concrete deterioration and loss in compressive strength and mass when the specimens were exposed to HCl acid solution. Further, less propagation of micro-cracks caused by expansive ettringite was observed in the case of MgSO4 attack. The RA-based concrete incorporated with sustainable SCMs exhibited significant benefits in terms of depletion of natural resources as well as reduction in CO2 emissions up to 30% compared to conventional concrete. Overall, the cement required for concrete production can be reduced using agricultural by-products, which are considered as waste materials and thus, the concrete produced using up to 30% of SCMs as a replacement for cement could be considered as more environmentally-friendly concrete.